K-State 2025 Strategic Direction Action Plan and Alignment for K-State First - Kansas State University, K-State First (Kansas State University. K-State First., 2013)
A strategic direction outline on how Kansas State University's K-State First initiative, comprised of the First Year Seminars, Connecting Across Topics (CAT) Communities, the K-State Book Network (KSBN), and Guide to Personal Success (GPS) program, envisions their 2025 plan to operate, with short-term, intermediate, and long-term expected outcomes. The strategic direction coincides with the university's strategic goal of becoming a top research institution within the United States.
Keywords: K-State 2025; First-year seminars; K-State Book Network (KSBN); GPS; CAT communities; Strategic plan; Papers (document genres)